KESELAMATAN KERJA DALAM PELAYANAN PENANGGULANGAN BENCANA DI BADAN PENANGGULANGAN BENCANA DAERAH KAB SIDOARJO - Seto Michiko (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
In accordance with Article 3 of the Minister of Manpower Regulation No. 05/1996, the Disaster Management Agency of the Sidoarjo Regency began introducing Occupational Health and Safety (K3) activities starting with introducing K3 management in 2000 who had obtained SMK3 certification. During the process of using internal auditors, companies also use external auditors every 3 years with fairly good results. This research is phenomenology using quantitative methods. The Number of samples in this studied 55 employees from the Sidoarjo Regional Disaster Management Agency population. From Knowledge Management variables, the Attitudes and Subjective Norms together towards Intentions were found to be 85.2%. While the remaining 14.8% is influenced by other variables not examined in this study, every increase in Knowledge Management (X1) of 1 unit, it will increase Intention (Y) by 0.325 units. Every increase in Attitude (X2) of 1 unit, it will increase Intention (Y) of 1,116 units. Each increase in Subjective Norms (X3) is 1 units, it will increase Intention (Y) by 0.203 units.